Noncovalent interaction mechanism and functional properties of flavonoid glycoside-β-lactoglobulin complexes. Issue 3 (17th January 2023) - Fu, Min; Gao, Lizhi; Geng, Qin; Li, Ti; Dai, Taotao; Liu, Chengmei; Chen, Jun
Abstract : Flavonoid glycoside-β-lactoglobulin complexes were formed via non-covalent interactions and the functional properties of complexes were improved through binding. Abstract : The interaction of flavonoid glycosides with milk protein and effects on the functional properties of flavonoid glycoside-β-lactoglobulin complexes are still inexplicit. The noncovalent interactions between flavonoid glycosides including quercetin (QE), quercitrin (QI), and rutin (RU) with β-lactoglobulin (β-LG) were determined by computer molecular docking and multispectral technique analysis. The fluorescence quenching results indicated that the flavonoid glycosides formed stable complexes with β-LG by the static quenching mechanism. The computer molecular docking and thermodynamic parameters analysis conclude that the main interaction of β-LG-QE was via hydrogen bonding, while for β-LG-QI and β-LG-RU it is via hydrophobic forces. The order of binding affinity to β-LG was QE (37.76 × 10 4 L mol −1 ) > RU (16.80 × 10 4 L mol −1 ) > QI (11.17 × 10 4 L mol −1 ), which indicated that glycosylation adversely affected the colloidal complex binding capacity. In this study, the physicochemical properties of the protein-flavonoid colloidal complex were determined. The analysis by circular dichroism spectroscopy demonstrated that flavonoid glycosides made the protein structure looser by inducing the secondary structure of β-LG to transform from the α-helix and β-sheet to random coils. The hydrophobicity of β-LG decreased due to binding with flavonoid glycosides, while functional properties including foaming, emulsification, and antioxidant capacities of β-LG were improved due to the noncovalent interactions. This study presents a part of the insight and guidance on the interactive mechanism of flavonoid glycosides and proteins and is helpful for developing functional protein-based foods.